Feeding patterns reprogram a gut microbial virulence–iron–quorum sensing functional axis linked to atherosclerotic risk - Zhang, He; Chen, Keyu; Chen, Renjin; Jia, Erteng (Frontiers in Microbiology, 2026)
The feeding rhythm is a major temporal regulator of metabolic physiology, yet its impact on microbiome-derived functional traits relevant to cardiometabolic disease remains insufficiently understood. Our previous work demonstrated that ad libitum, daytime-restricted, and nighttime-restricted feeding produce markedly different atherosclerotic outcomes in Apoe−/− mice, indicating that the feeding rhythm acts as a modifiable determinant of atherogenic susceptibility. Here, we used shotgun metagenomics to profile risk-associated microbial functional modules—including Type III and Type VI secretion systems (T3SS/T6SS), siderophore-based iron acquisition pathways, quorum-sensing (QS) regulators, and antimicrobial resistance determinants—across feeding regimens. The feeding rhythm induced pronounced functional segregation independent of α-diversity, which was consistent with selective functional reprogramming rather than taxonomic restructuring. Daytime feeding, which is misaligned with the murine active phase, is associated with coordinated enrichment of the T3SS/T6SS, iron uptake, and QS pathways, forming a tightly interconnected “virulence–iron–QS–ARG” functional consortium. In contrast, circadian-aligned nighttime feeding resulted in attenuated virulence orientation and enhanced metabolic-cooperative signatures. Network inference further revealed strong coactivation of virulence secretion, iron mobilization, and QS modules under circadian misalignment. These findings show that the feeding rhythm modulates atherogenic susceptibility not only through host metabolism but also by remodeling gut microbial functional capacities, highlighting microbial functional ecology as an integral component of diet–host interactions.